A Study of Neogene Sedimentary Outcrops of the Greater Miri Area - Can Clay Gouging Be Calibrated in Outcrops and Shallow Subsurface Boreholes? - Franz L. Kessler; John Jong (Ikatan Ahli Geologi Indonesia, 2017)
The greater Miri area offers particularly well-exposed world-class examples of fault geometry and clay gouging. Such information offers good material for studying fault architecture and clay smear morphology, and help to understand fault seal mechanisms in the subsurface. Recent studies on fault and clay gouging in the Neogene sedimentary rocks of greater Miri area show a variety of fault geometries of both abrasive-type and shear-type. In a Nippon Oil-sponsored study carried out in Curtin University, fifteen (15) core holes were drilled through clay-gouged fault planes at three outcrop locations. Cores of the formation were taken, and the drilled holes were then pressurized by water injection for packer testing. The performed leak-off test results were somewhat surprising - weathered Neogene sediments of the Miri and Tukau formations offered little or no pressure retention in fault zones and host rock alike, and leak-off fracturing occurs already at 1.25 bar. The rock mechanics of weathered rock might be very different from fresh rock, and may offer little or no insight into those of virgin rocks. Therefore, weathered rock properties may not be suitable for subsurface fault seal simulation studies.